PENGARUH KOMPETENSI GRAMMAR DAN PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MEMBUAT SURAT BISNIS BERBAHASA INGGRIS PADA PROGRAM STUDI ADMINISTRASI BISNIS DI POLITEKNIK LP3I JAKARTA KAMPUS CILEUNGSI - Diand Mardiana; Ayi Kamaludin; S Sutrisno (JURNAL LENTERA BISNIS, 2018)
ABSTRACTThe purpose of the research is to test and to analyze the hypothesis about the effects of grammar competences and vocabulary mastery on writing skill of making English business letter. The research has been done by the methodology of survey. The population is the students of business administration program at private polytechnic LP3I Jakarta campus Cileungsi. The number of samples is 74. The samples are distributed in the first level until the last level of the program. The research used random sampling as sampling technique for determining which part of population will be a sample. The instrument has been used on this research is vocabulary mastery test. The test is divided into two. The first is general English vocabulary test and the second is business English vocabulary test. The general English vocabulary test consists of 30 numbers multiple choice questions and the business English vocabulary test consists of 20 numbers multiple choice questions and 5 matching questions.Keywords : grammar competence, vocabulary mastery, writing skill on making English business letter.